Test On The Implementation of Compound Biodive Poc Inincreasing The Germination Rate of Sugar Cane Cuttings (Sugar Factoryl.) - Sri Purwanti; Shodikun Adim; Nurul Huda; Nurlina (Agricultural Science, 2023)
The aim of this research was to determine the effect of various concentrations of compound biological liquid organic fertilizer (POC) on the germination of plant cuttings. This research method uses a Randomized Group Design (RAK), with 1 treatment factor, namely Biological POC Concentration (K) consisting of 8 treatment levels, namely 0 ml, 1 ml, 2 ml, 3 ml, 4 ml, 5 ml, 6 ml, and 7 ml Biological POC per liter of water. This experiment was repeated 3 times with each treatment containing 2 sample plants, so that 24 treatments were obtained. Results The best statistical value was achieved by the K4 treatment, namely a concentration of 4 ml of Biological POC per liter of water for all observed parameters, including the percentage increase in growth compared to the control treatment so that the K4 treatment was considered more effective and efficient in the initial growth of sugarcane cuttings.